KASIRA Media: A Simple Sentence Application Based on Jepara Culture for 2nd Grade Elementary School Students (Feasibility and Practicality) - Duta Risma Pradita; Rani Setiawaty; Novia Rohman; Farikhahtus Saniyyah (Jurnal Prajaiswara, 2026)
Introduction/Main Objectives: This study aims to develop, test the feasibility and practicality of the KASIRA (Simple Sentences from Jepara) application as an innovative digital learning media to improve the simple sentence writing skills of second-grade elementary school students. Research Methods: The method used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The application was developed by integrating the Canva, Heyzine, and AppGeyser platforms, and includes local Jepara wisdom. The feasibility test was carried out by media experts and material experts, while the practicality test was measured through teacher and student responses. Finding/Results: The validation results showed that KASIRA was declared very feasible with an average score of 92.25% from media experts and 93.5% from material experts. The results of the practicality test were also in the very practical category with a score of 95% from teachers and 96.1% from students. This application was considered interesting, easy to use, and relevant to the local cultural context of Jepara. Novelty: This research lies in the integration of Jepara local wisdom (such as carvings and coastal activities) into learning media for writing simple sentences based on Android educational games, which are specifically designed for grade II elementary school students in Phase A.